Increased inflammatory status and higher prevalence of three-vessel coronary artery disease in patients with concomitant coronary and peripheral atherosclerosis - Brevetti, Gregorio; Piscione, Federico; Silvestro, Antonio; Galasso, Gennaro; Di Donato, AnnaMaria; Oliva, Gabriella; Scopacasa, Francesco; Chiariello, Massimo (Thrombosis and Haemostasis, 2003)
The aim of this study was to determine whether patients with coronary artery disease (CAD) and concomitant peripheral arterial disease (PAD) have a greater inflammatory status than those with CAD alone. To this aim, we evaluated PAD (ankle/brachial pressure index <0.9), and measured plasma levels of C-reactive protein (CRP), interleukin-6 (IL-6) and the soluble forms of intercellular adhesion molecule-1 (sICAM-1) and vascular cell adhesion molecule-1 (sVCAM-1) in 234 patients who underwent coronary angiography. Median levels of CRP, IL-6 and sICAM-1 were higher in the CAD without PAD (n=134) and CAD+PAD (n=40) groups than in 60 patients without either disease (“controls”). Median CRP values were higher in patients with CAD+PAD than in patients with CAD alone (4.7 mg/L [1.5;7.6] vs 2.4 mg/L [0.9;3.8], p < 0.01). Three-vessel CAD was diagnosed in 60% of CAD+PAD patients and in 21% (p< 0.01) of CAD only patients. After adjustment for confounding factors, only PAD was independently associated with three-vessel CAD (p<0.001). This association was maintained after adjustment for IL-6, the only inflammatory parameter significantly associated with three-vessel CAD at univariate analysis (p<0.01). In conclusion, in CAD the coexistence of PAD is associated with a greater inflammatory status and more widespread coronary atherosclerosis. These results could help to explain the high cardiovascular risk of patients with concomitant CAD and PAD and suggest that PAD be included among the variables used to identify CAD patients for further diagnostic evaluation.
Keywords: Coronary artery disease; peripheral arterial disease; inflammation; adhesion molecules